Komunikasi Interpersonal Pada Pasangan Pernikahan Dini - Hidayat, Arif; , Dra. Zahrotul Uyun, M.Si (2016)
Marriage is a procession that arranged in such a way to legalize a pair of male and female relationships. There are many marriage phenomenon in the society. One is the phenomenon of early marriage. Early marriage is a marriage that commited under the age of which has been governed by law. It is undeniable that one of the purposes of marriage is to create an harmonic family condition. Harmonic family can happen if the communication between individuals who are in the family is created properly. This study aims to determine the interpersonal communication that occurs on a pair of early marriage. The method in this research using qualitative methods. The subjects of this research were 10 people who were 5 couples who did early marriage. Methods of data collection using interviews and review of documentation. The results of this study indicate that the marriages at young age will still work if the marriage is accompanied by the readiness of each partner to raise a family. Good communication, which is empathic, transparency, mutual support, build closeness, positive thinking and mutual respect will make the relationship between husband and wife in a family has become harmonic.